Mechanical and Microstructural Characterization of an Aluminum Bearing Trip Steel - Bustos-Castillo, O; Monsalve-Gonzalez, A; Carvajal-Ortega, L; Artigas-Abuin, A (Springer Boston, 2016)
The mechanical properties and microstructural characteristics of a steel able to sustain the TRIP-effect were studied. The material was prepared by taking in mind the partial substitution of silicon by aluminum following a processing route that included hot forging, hot and cold rolling, intercritical annealing, and a final bainitic isothermal treatment. The mechanical properties that were obtained resulted to be above those of commercial a 780 TRIP steel. The TRIP phenomenon was confirmed by the change in retained austenite before and after deforming the steel; X-ray diffraction was used to evaluate the volume content of retained austenite. Formability of the steel under study can be rationalized in terms of the texture developed in the material. © 2016, The Minerals, Metals & Materials Society and ASM International.